Comparison between Carotid Artery Wall Thickness Measured by Multidetector Row Computed Tomography Angiography and Intimae-Media Thickness Measured by Sonography - Živorad N. Savić; Ivan I. Soldatović; Milan D. Brajović; Aleksandra M. Pavlović; Dušan R. Mladenović; Vesna D. Škodrić-Trifunović (The Scientific World Journal)
The increased thickness of the carotid wall >1 mm is a significant predictor of coronary and cerebrovascular diseases. The purpose of our study was to assess the agreement between multidetector row computed tomography angiography (MDCTA) in measuring carotid artery wall thickness (CAWT) and color Doppler ultrasound (CD-US) in measuring intimae-media thickness (IMT). Eighty-nine patients (aged 35–81) were prospectively analyzed using a 64-detector MDCTA and a CD-US scanner. Continuous data were described as the mean value ± standard deviation, and were compared using the Mann–Whitney U test. A p value <0.05 was considered significant. Bland–Altman statistics were employed to measure the agreement between MDCTA and CD-US. CAWT ranged from 0.62 to 1.60 mm, with a mean value of 1.09 mm. IMT ranged from 0.60 to 1.55 mm, with a mean value of 1.06 mm. We observed an excellent agreement between CD-US and MDCTA in the evaluation of the common carotid artery thickness, with a bias between methods of 0.029 mm (which is a highly statistically important difference of absolute values [t = 43.289; p < 0.01] obtained by paired T test), and limits of agreement from 0.04 to 0.104. Pearson correlation coefficient was 0.9997 (95% CI 0.9996–0.9998; p < 0.01). We conclude that there is an excellent correlation between CAWT and IMT measurements obtained with the MDCTA and CD-US.